Fragmentation and particle production in deep inelastic scattering and photoproduction - Tymieniecka, Teresa (Array, 2008)
Summary: Charged particle production has been studied in deep inelastic scattering with the H1 and ZEUS detectors at HERA. The evolution of scaled momentum distribution with respect to Q2 is shown in the current fragmentation region of the Breit frame in the range from 10 to 40000 GeV2. Characteristics of the produced particle are presented for (anti)deuteron, (anti)protons, kaon pair production as well as (anti)lambda and K⁰